Growth promoting and immunomodulatory effects of dietary Moringa oleifera leaf powder in rainbow trout (Oncorhynchus mykiss) - Narjes Sanchooli; Hamed Paknejad; Mohammad Sudagar; Seyed Pezhman Hosseini Shekarabi; Abdolali Rahdari (Aquaculture Reports, 2023)
This study aimed to manifest the dietary effect of Moringa oleifera (MO) leaf powder on growth performance and immunity in rainbow trout before and after Aeromonas hydrophila infection. The fish (N = 360; 35.49 ± 0.50 g) were fed with incremental levels of MO at 0, 10, 25, and 50 g/kg for eight weeks and then challenged with A. hydrophila for 10 days in triplicates. The final weight (114.6 g) and feed conversion ratio (1.28) were significantly decreased in MO-50 compared to other MO-added groups (P < 0.05). In the unchallenged fish, the total white blood cells (WBC), lymphocyte, and neutrophil population size did not change between the experimental and the control groups (P < 0.05), while after the bacterial infection, the number of circulating lymphocytes and WBC were significantly increased in both MO-25 and MO-50 groups compared to the control group. Before the challenge test, the expression level of lysozyme gene in the head kidney was significantly (P < 0.05) increased in all MO-added groups, while the serum and skin mucus lysozyme, bactericidal, and complement activities were notably increased in MO-25 group. A similar trend was observed in the expression levels of IL-1β and TNF-1α genes in the head kidney of MO-added groups, while the total mucus immunoglobulin and protein levels were elevated in both MO-25 and MO-50 groups. The expression levels of SOD, CAT, and GPx genes were markedly down-regulated in MO-25 compared to the control group pre- and post-challenge test. The fish survival rate after challenging with A. hydrophila significantly increased from 46.7% in the control group to 76.7% in MO-25 group. In conclusion, using the supplemental diets with MO for rainbow trout at 19.3–25.0 and 27.5–30.5 g/kg is recommended based on the polynomial regression analyses to accelerate growth performance and provide immunostimulation, respectively.